High Frequency Inverter with Fuzzy Logic Controller for Portable Induction Heater - Ummah, Karunia Vio Nita Rusyatul; Eviningsih, Rachma Prilian; Windarko, Novie Ayub (Emitor: Jurnal Teknik Elektro, 2024)
The development of technology today makes humans strive to save natural resources and switch to alternative energy. For reasons of saving energy, saving costs, easy to use, and having a high level of safety, induction heaters can be used as an alternative to overcome these problems. Induction heaters can generate heat through the process of electromagnetic induction when cookware made of metal is brought closer. In this process the coil is supplied with alternating electric current from a high frequency inverter which then induces the cookware with metal material to cause heat. The heat in the induction heater will be regulated through the switching frequency of the high-frequency inverter which gets its voltage source from a 24V battery and increases the voltage to 48V. This induction heater is designed to maintain the setpoint temperature 70°C and 100°C using fuzzy logic control. From the test results it can be seen that the fuzzy logic control can reach a setpoint temperature of 70°C within 20 minutes and after being disturbed the fuzzy logic control can maintain the setpoint temperature with an error percentage of around 0.14% - 0.29%. Meanwhile, the setpoint temperature of 100°C can be achieved within 35 minutes and after being disturbed the fuzzy logic control can maintain the setpoint temperature with an error percentage of around 0.14% -0.9%.